Observing and Understanding the Ultrafast Photochemistry in Small Molecules: Applications to Sunscreens. (September 2016) - Baker, Lewis A.; Stavros, Vasilios G.
In this review, we discuss the importance of biological and artificial photoprotection against overexposure to harmful ultraviolet radiation. Transient electronic and transient vibrational absorption spectroscopies are highlighted as important tools in understanding the energy transfer in small molecules, with a focus on the application to commercial sunscreens with representative examples given. Oxybenzone, a common ingredient in commercial sunscreens and sinapoyl malate, a biological sunscreen in plant leaves are presented as case studies.